The Implementation of Satupadu.Id Digital Platform for Prospective Tutoring Teachers - Setiani, Ani; Budiarti, Isniar; Novendra, Afief Maula; Almujab, Saiful; Indriani, Rina; Hamdani, Acep Roni (RGSA : Revista de Gestão Social e Ambiental, 2024)
Purpose: The purpose of this research is to identify the implementation of the satupadu.id mobile-based tutoring booking application as an effort to accelerate the improvement of the quality of education.